Analysis of the Transmission Accuracy of Worm and Gear Combined Mechanism - Yang Kai; Hu Xiaoqiu; Zhao Lei; Qin Liyu (Jixie chuandong)
Based on the rotary table of MCH50 machining center,a transmission accuracy model of combined mechanism is established by considering the process error,eccentric error,phase angle,load and deformation and so on. The model is verified by the calculation of driving mechanism,the result show that the integrated transmission error is consistent with the experimental result. On this basis,the influence of the distribution of the velocity ratio and center distance of gear on transmission accuracy is analyzed.